KETAHANAN SERANGAN PENYAKIT KARAT TUMOR PADA UJI KETURUNAAN SENGON (Falcataria moluccana) DI BONDOWOSO, JAWA TIMUR - Setiadi, Dedi; Susanto, Mudji; Baskorowati, Liliana (Jurnal Pemuliaan Tanaman Hutan, 2014)
As a part of tree improvement project of sengon (Falcataria moluccana L. Nielsen) several progeny test were established in December 2011. One of those progeny test was established in Bondowoso, East Java. Row Column Desgin (Incomplete Block Design) was used as experimental design involving 70 families (9 Papua provenance and 1 provenance Solomon), 4 replications (blocks), 4 trees per plot and a spacing of 3 x 2 m. Observations were made at the age of 6 and 12 months, including recorded the percent of survival plants, height, diameter and the gall rust incidence. Results showed that in general, the early growth of individual plant in this plot demonstrated a fairly good performance with the survival rate of 98.5% (6 months old), and 96.9% (1 year old). The early growth of sengon varied significantly between provenances. The best growth demonstrated by provenances from Meagama, Holima and Hobikosi. Early estimation of individual heritability of plant height categorised in low (h2i= 0.07 to 0.11, h2f= 0.16 to 0.21), whereas individual heritability of diameter were catagorised in medium (h2i= 0, 08 to 0.27, h2f= 0.15 to 0.43). Moreover, the positive value of the genetic correlation revealed between height and diameter (0.88 and 0.85). Several individual trees originated from Holima, Meagama and Elagaima exhibited 0% of gall rust disease incidence.